2016
DOI: 10.1109/jlt.2016.2554145
|View full text |Cite
|
Sign up to set email alerts
|

LED Based Wavelength Division Multiplexed 10 Gb/s Visible Light Communications

Abstract: LED based Visible Light Communications can provide high data rates to users. This can be further increased by the use of wavelength division multiplexing, using the different colours required to generate white light to transmit different data streams. In this paper a trichromatic approach is described, and the influence of colour combination on achievable data rate is analysed. A demonstration of LED based communications which achieves a data rate of >10 Gb/s by using a rate adaptive orthogonal-frequency-divis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 198 publications
(103 citation statements)
references
References 20 publications
0
103
0
Order By: Relevance
“…Basically, there are two possible approaches. The first one is referred as Wavelength Division Multiplexing (WDM) and considers each HB-LED as an independent transmitter, thus achieving three channels with a bandwidth of around 20 MHz for each one [20]- [25]. The second approach is known as Color-Shift Keying (CSK) and is a modulation scheme that transmits data by performing small variations of the light color [26]- [28].…”
Section: Techniques For Enhancing the Available Bandwidthmentioning
confidence: 99%
See 2 more Smart Citations
“…Basically, there are two possible approaches. The first one is referred as Wavelength Division Multiplexing (WDM) and considers each HB-LED as an independent transmitter, thus achieving three channels with a bandwidth of around 20 MHz for each one [20]- [25]. The second approach is known as Color-Shift Keying (CSK) and is a modulation scheme that transmits data by performing small variations of the light color [26]- [28].…”
Section: Techniques For Enhancing the Available Bandwidthmentioning
confidence: 99%
“…The key point is that considering the use of the same bandwidth enhance techniques for both pulse-based and efficient modulation schemes, the last ones achieve higher bit rates. The combination of efficient modulation schemes and different techniques for enhancing the available bandwidth can be found in [21]- [25] and [42]- [45].…”
Section: Modulation Schemes and Proposed Hb-led Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…With a non-linear LED response compensation using a Volterra based equalizer, Wang et al demonstrated 4.5 Gb/s system using an RGB LEDs [45] and 8 Gb/s using an RGBY LEDs [6]. Chun et al studied the impact of the different color combination on the communication system and theoretically established an achievable data rate for different RGB color combinations [5]. A > 10 Gbits/s WDM VLC system was demonstrated by using the simultaneous reception of the entire channels.…”
Section: Wavelength Division Multiplexing (Wdm)mentioning
confidence: 99%
“…Besides optical filtering, a number of advanced and computationally complex techniques had been devised to overcome the bandwidth limitation. As a result, the achievable data rate grew from a humble 100's of Mb/s in 2007 [3], [4] to 10's of Gb/s in 2016 [5]- [7]. In order to make the Gb/s data rate feasible with a low bandwidth system, a number of advanced and computationally complex technologies have been adopted.…”
Section: Introductionmentioning
confidence: 99%